Fall incidence and associated risk factors among people with a lower limb amputation during various stages of recovery – a systematic review. Issue 15 (17th July 2019) - Steinberg, Noam; Gottlieb, Amihai; Siev-Ner, Itzhak; Plotnik, Meir
Abstract: Purpose: The objective of this study was to estimate fall incidence and describe associated risk factors among people with a lower limb amputation (LLA) during various stages of recovery: the surgical ward, in-patient rehabilitation and return to community life. Materials and methods: A systematic search of relevant English language articles was performed using PubMed and EMBASE. Out of 310 initial "hits, " six retrospective cohort studies, one prospective cohort study and eleven cross-sectional studies from which fall incidence and risk factors could be extracted, were selected for critical review. Fall incidence and associated risk factors were extracted and analyzed in the context of various clinical stages of recovery after amputation. The studies were evaluated for quality using the "Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies." Results: Results showed that during all stages of recovery, people with a LLA are at increased risk of falling compared with able-bodied individuals, as well as other clinical populations. Each stage of recovery is associated with different fall risk factors. The current review is limited mainly by the paucity of studies on the topic. Conclusions: Specialised care focusing on the most relevant risk factors for each stage of recovery may enhance fall prevention during post-fall recovery. Implications for rehabilitation:   People with a lower limb amputation are at a high risk of falling in all stages of their clinical course.        Health professionals should be aware that people with a lower limb amputation in the first 4 years ofamputation or with four or more health-related problems are at an increased risk.        Health professionals should also be aware that increased gait variability, excess confidence in balance andwalking abilities and less cautious stair walking, impose an elevated risk of falling and should focus theirefforts in reducing these factors.